ANALISIS KECELAKAAN KERJA MENGGUNAKAN METODE HIRARC (HAZARD IDENTIFICATION, RISK ASSESSMENT DAN RISK CONTROL) DI DIVISI MAINTENANCE CV. DIRA UTAMA SEJAHTERA - Muhammad Adi Purwanto; Akhmad Wasiur Rizqi; Hidayat Hidayat (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2022)
Human resources are an important asset in a company and need to be developed. Human resource development is related to the performance generated in achieving the company's targets. The sustainability of human resource performance cannot be separated from work accidents. Many factors often cause work accidents such as: human error, electric shock, etc. This study aims to identify potential hazards, calculate risk level values, analyze the results of risk assessment calculations, and propose controls and solutions to reduce potential hazards and work accidents. The research was conducted in the maintenance division of CV. Dira Utama Sejahtera. It’s a manufacturing company engaged in the field of line pipe. The research was conducted using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method. The results showed that there were 9 potential hazards, namely collision on the feet or head, electric shock, falling from the pipeline, pinched between pipelines, chemical explosion, hands hit by hot pipes, splashed by material, hands hit by drill bits, and slipped until the leg is sprained. The results of the risk level assessment that 11,1% fall into the category of low risk and extreme, 33,3% moderate risk, and 44,4% high risk. For risk control, it is proposed by elimination, administrative control, engineering control, and the use of Personal Protective Equipment (PPE).Keywords  : Work Accidents, Line Pipe Company, HIRARC Method